Development of a Construction Service Provider Performance Assessment System as an Instrument for Preventing Project Failure in the Badung Regency Government - I Wayan Gede Putrawan; I Gede Putu Kawiana; I Putu Putra Astawa (SEAN Institute, 2026)
The failure of government construction projects characterized by work delays, the imposition of fines, and even contract termination remains a challenge in the implementation of government procurement of goods/services. This study aims to analyze the influence of construction service provider performance on the risk of project failure in Badung Regency and identify the most dominant performance dimensions in shaping service provider performance. The study used a quantitative approach with an explanatory research design. Data were obtained from 140 respondents consisting of Commitment Making Officers (PPK), technical officials, and construction service providers involved in Badung Regency government projects. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that all service provider performance dimensions, namely technical performance, time performance, financial performance, managerial performance, and contractual compliance, had a positive and significant effect on service provider performance. The managerial performance dimension was the most dominant factor with an influence coefficient of 0.365, followed by contractual compliance at 0.241. Service provider performance was proven to have a significant effect on the risk of project failure (b= 0.246; p = 0.024), although its contribution is relatively limited with an R² value of 0.060. This finding indicates that improving service provider performance can be an important instrument in mitigating project risks, but preventing project failure also requires strengthening aspects of planning, governance, supervision, and risk management in an integrated manner. This study recommends the development of a service provider performance assessment system based on historical data as a basis for more accountable procurement decisions that are oriented towards project success.